2015
DOI: 10.1590/1982-43272560201514
|View full text |Cite
|
Sign up to set email alerts
|

The Absence of Generosity and Obedience to Authority: Judgments of Teachers and Students From Kindergarten

Abstract: Preschool Education can provide conditions for the construction of moral values in children. This study’s objective was to investigate the judgment of teachers and students in Primary Education regarding the virtue of generosity and whether, in this judgment, it is valued more than obedience to authority. Interviews were held with 26 teachers and 90 children from four municipal schools, using a stimulus-story about an activity using modeling clay. The results indicated that, for the majority of participants, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…Gratitude is present in the life of youth who live in different contexts (Paludo, 2014), features as a part of young adolescents' conceptions of what it takes to be considered a moral person (Hardy, Walker, Olsen, Skalski, & Basinger, 2011), and develops during childhood and adolescence (Baumgarten-Tramer, 1938;Freitas et al, 2011;Piaget, 1954Piaget, /1981 as children form a theory of mind, are able to think in non-egocentric ways, and can take into account others' intentionality (Kawashima & Martins, 2015). We should thus expect youth of different ages to express gratitude in different ways.…”
mentioning
confidence: 99%
“…Gratitude is present in the life of youth who live in different contexts (Paludo, 2014), features as a part of young adolescents' conceptions of what it takes to be considered a moral person (Hardy, Walker, Olsen, Skalski, & Basinger, 2011), and develops during childhood and adolescence (Baumgarten-Tramer, 1938;Freitas et al, 2011;Piaget, 1954Piaget, /1981 as children form a theory of mind, are able to think in non-egocentric ways, and can take into account others' intentionality (Kawashima & Martins, 2015). We should thus expect youth of different ages to express gratitude in different ways.…”
mentioning
confidence: 99%
“…In these cases, teacher training is aimed in one direction, while the road map marked out by the administration goes in another. Recent studies have shown that even in the very early stages of schooling, obedience to authority is a value within schools (Kawashima & Martins, 2015).…”
Section: Some Conclusion: Practices Of Resistance In Schoolsmentioning
confidence: 99%
“…So when I get off the drug, it's as if a normal person drank coffee… He may have been losing confidence in his body, but the pill enhanced Zach's ability to recall difficult material for exams, and it gave him the obedience he needed to build social capital and conformity to the curriculum standards and expectations. Some education literature involving kindergarten children describes how teachers may prioritize implementing obedience into children rather than a moral value system (Kawashima & Martins, 2015). The comparison here is rich: while the pill made Zach question the curriculum less, his newfound obedience sparked a revelation that the university program was molding and infantilizing him into a person he did not want to be.…”
Section: Zach's Storymentioning
confidence: 99%